Neoliberalism, pedagogy and human development : exploring time, mediation and collectivity in contemporary schools - Kontopodis, Michalis (New York : Routledge, 2012)
"In most Western developed countries, adult life is increasingly organized on the basis of short-term work contracts and reduced social security funds. In this context it seems that producing efficient job-seekers and employees becomes the main aim of educational programs for the next generation. Through case studies of Turkish and Arabic students in Berlin (Germany), Asian, Hispanic and Black students in Long Beach (USA), and children of landless rural workers in Espirito Santo (Brazil), this book investigates emerging educational practices and takes a critical stance towards what can be seen as "mainstream" or "dominant" educational politics. Kontopodis poses the question of whether encouraging students to engage in guided reflection about themselves, their past performance and their future career supports marginalized youth in dealing with complex everyday situations and actively participating in societal improvement. His interdisciplinary theoretical account draws on process philosophy and time theory, developmental and educational psychological theorising (mainly Vygotskian/post-Vygotskian), sociology of education, as well as on continuing discussions in the fields of science and technology studies and anthropology. The book suggests an innovative relational understanding of time and development at school which can prove of particular importance for the education of marginalized students"-- Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Education -- Social aspects -- Cross-cultural studies; Critical pedagogy -- Cross-cultural studies; Minorities -- Education -- Cross-cultural studies; Neoliberalism -- Cross-cultural studies; Electronic books